2022
DOI: 10.1007/s11356-022-19448-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of PM2.5 and its components with lengths of hospital stay for hand foot and mouth disease in children

Abstract: BackgroundHand foot and mouth disease (HFMD) is a public health concern. Studies on air pollution and the lengths of hospital stay (LOS) of HFMD are scarce. MethodsWe characterized the clinic demographic features of 5135 hospitalized HFMD in Nanjing, China from 2012 to 2017, and analyzed the association between short-term exposure to PM 2.5 as well as its components (OM, BC, SO4 2− , NH4 + , NIT, SOIL and SS) and the LOS of HFMD. ResultsAmong them 98.62% were aged 0-6 years old, and 3772 (73.46%) were hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, evidence on the association between sulfate and infections is still lacking. A recent study observed that exposure to sulfate particles was associated with increased length of stay from hand-foot-mouth disease 29 . One potential mechanism for the observed effect could be that acidic sulfates turn the metal oxides from PM2.5 into metal ions which are soluble in the lung lining fluid, producing oxidative compounds and ultimately perturb the immune system [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence on the association between sulfate and infections is still lacking. A recent study observed that exposure to sulfate particles was associated with increased length of stay from hand-foot-mouth disease 29 . One potential mechanism for the observed effect could be that acidic sulfates turn the metal oxides from PM2.5 into metal ions which are soluble in the lung lining fluid, producing oxidative compounds and ultimately perturb the immune system [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%